2010
DOI: 10.1177/1934578x1000500107
|View full text |Cite
|
Sign up to set email alerts
|

New Antiinflammatory Sterols from the Red Sea Sponges Scalarispongia aqabaensis and Callyspongia siphonella

Abstract: Bioassay-guided fractionation of the anti-inflammation fractions of the Red Sea sponges Scalarispongia aqabaensis and Callyspongia siphonella yielded two new sterols from chloroform fractions of methanol extracts, namely scalaristerol (5α,8α-dihydroxycholest-6-en-3β-ol) (1) from Scalarispongia aqabaensis, and callysterol (ergosta-5,11-dien-3β-ol) (2) from Callyspongia siphonella. Structure determination was based on extensive NMR studies and mass spectrometry. The antiinflammatory activity of compounds 1 and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 17 publications
0
33
0
Order By: Relevance
“…Previous studies have shown that phytosterols exert various biological effects such as anti-cancer, anti-pyretic and immune-modulating activities (Gupta et al, 1980;Raicht et al, 1980;Bouic et al, 1996;Bouic et al, 1999). In addition, their antiinflammatory activities are also well demonstrated (Navarro et al, 2001;Okoye et al, 2010;Youssef et al, 2010). The role of phytosterols in rheumatoid arthritis (RA) has been investigated previously (Thiers, 1953).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that phytosterols exert various biological effects such as anti-cancer, anti-pyretic and immune-modulating activities (Gupta et al, 1980;Raicht et al, 1980;Bouic et al, 1996;Bouic et al, 1999). In addition, their antiinflammatory activities are also well demonstrated (Navarro et al, 2001;Okoye et al, 2010;Youssef et al, 2010). The role of phytosterols in rheumatoid arthritis (RA) has been investigated previously (Thiers, 1953).…”
Section: Introductionmentioning
confidence: 99%
“…Previous investigation of the Red Sea Didemnum species led to the isolation of two new spiroketals, didemnaketals D and E (Mohamed et al 2014). In continuation of our investigation of the same species, we describe here the isolation and structural elucidation of two new glycerides named didemnacerides A (1) and B (2), along with three known sterols, 24-ethyl-25-hydroxycholesterol (3) (Siddiqui et al 1989), cholest-6-en-3,5,8-triol (4) (Youssef et al 2010) and cholestane-3b,5a,6b-26-tetrol (5) (Liyanage & Schmitz 1996). Compounds 3 -5 are reported here for the first time from the Red Sea ascidian Didemnum species (Figure 1).…”
Section: Introductionmentioning
confidence: 93%
“…The compounds were identified as 24-ethyl-25-hydroxycholesterol (3) (Siddiqui et al 1989), cholest-6-en-3b,5a,8a-triol (4) (Youssef et al 2010) and cholestane-3b,5a,6b-26-tetrol (5) (Liyanage & Schmitz 1996).…”
Section: Natural Product Research 1593mentioning
confidence: 99%
“…Asolkar and colleagues described two new cyclohexadepsipeptides arenamides A and B ( 105 , 106 ), isolated from the Fijian bacterium Salinispora arenicola , that inhibited LPS-induced murine macrophage RAW 264.7 cells PGE 2 and NO production in vitro , by affecting NFκB signaling activity (IC 50 = 3.7 and 1.7 μM, respectively), thus highlighting their “anti-inflammatory characteristics” [107]. Three publications yielded potentially novel compounds targeting proinflammatory mediators released by activated brain microglia, a macrophage involved in neuroinflammation and neurodegeneration [151]: Youssef and colleagues described a new steroid callysterol ( 107 ) from the Red Sea sponge Callyspongia siphonella , which potently inhibited rat hind paw edema with an activity close to cortisone, and also reduced TXB 2 release from LPS-activated rat brain microglia (apparent IC 50 > 10 μM) [108]. Jean and colleagues observed that the sesquiterpene capnellene ( 108 ) isolated from the Indonesian soft coral Capnella imbricate , attenuated expression of inducible cyclooxygenase-2 both in activated microglia in vitro and in vivo , suggesting it might contribute to “the search for new therapeutic agents for treatment of neuroinflammatory diseases” [109].…”
Section: Marine Compounds With Antidiabetic and Anti-inflammatory mentioning
confidence: 99%